New radiological contributions to low digestive tract bleeding: Part I - Tiscornia, Eduardo; Sálice, Mario; Pizarrosa, Carlos (Cirugía del Uruguay, 1983)
Eventought severe digestive bleeding is in the mayority of cases a high bleeding, low bleeding can be very problematic.